Potassium ferricyanide oxidizes silicon quantum dots under alkaline conditions to produce chemiluminescence for uric acid detection in human urine. (22nd July 2022) - Song, Mengling; Huang, Mingyan; Yang, Zixin; Chen, Funan
Abstract: Potassium ferricyanide (K3 (Fe(CN)6 )) could directly oxidize silicon quantum dots (Si QDs) to generate chemiluminescence (CL) under alkaline conditions. It was noteworthy that in the Si QDs–K3 (Fe(CN)6 )–NaOH CL system, the Si QDs worked as a new luminescent material. In addition, the signal intensity of this CL system could be weakened with the addition of uric acid (UA). Based on these, we exploited a new easy and convenient determination method of UA. This method only needed filtration and dilution of UA, without other pretreatment. The constructed system exhibited a linear relationship that ranged from 0.50 to 4.50 mmol·L −1, with 0.24 mmol·L −1 of detection limit, and this system had successfully demonstrated the detection of UA in human urine. In addition, this work also broaden the application of the Si QDs in CL research. Abstract : Silicon quantum dots were synthesized using a hydrothermal method. Potassium ferricyanide could directly oxidize silicon quantum dots to generate chemiluminescence under alkaline conditions. The chemiluminescence signal is reduced when uric acid is added. Therefore, a chemiluminescence system was constructed to detect uric acid in human urine.